Mantle rock exposures at oceanic core complexes along mid-ocean ridges - Ciazela, Jakub; Koepke, Juergen; Dick, Henry J.B.; Muszynski, Andrzej (Geologos, 2015)
The mantle is the most voluminous part of the Earth. However, mantle petrologists usually have to rely on indirect geophysical methods or on material found ex situ. In this review paper, we point out the in-situ existence of oceanic core complexes (OCCs), which provide large exposures of mantle and lower crustal rocks on the seafloor on detachment fault footwalls at slow-spreading ridges. OCCs are a common structure in oceanic crust architecture of slow-spreading ridges. At least 172 OCCs have been identified so far and we can expect to discover hundreds of new OCCs as more detailed mapping takes place. Thirty-two of the thirty-nine OCCs that have been sampled to date contain peridotites. Moreover, peridotites dominate in the plutonic footwall of 77% of OCCs. Massive OCC peridotites come from the very top of the melting column beneath ocean ridges. They are typically spinel harzburgites and show 11.3–18.3% partial melting, generally representing a maximum degree of melting along a segment. Another key feature is the lower frequency of plagioclase-bearing peridotites in the mantle rocks and the lower abundance of plagioclase in the plagioclase-bearing peridotites in comparison to transform peridotites. The presence of plagioclase is usually linked to impregnation with late-stage melt. Based on the above, OCC peridotites away from segment ends and transforms can be treated as a new class of abyssal peridotites that differ from transform peridotites by a higher degree of partial melting and lower interaction with subsequent transient melt.